Pemahaman Peraturan Perpajakan, Tarif Pajak dan Asas Keadilan Terhadap Kepatuhan Wajib Pajak - HERRY APRILIA MANUBULU (Ekopem: Jurnal Ekonomi Pembangunan, 2020)
The study aims to know the effect that understanding tax regulations, tax tariffs and principles of justice have on individual tax compliance. Total of 47 umkm in the five coconut district. Research shows that variables of understanding tax regulations significantly affect tax compliance. This result can be proven with a greater t-count than t-table (2.329 > 2.017) and a significant test result shows a degree of significance of 0.021 smaller than 0.05 (0.021 < 0.05). Further tax rates have significant positive impact on taxpayers' compliance. This result can be proved by a value of t count > t tables (2.371 > 2.017) and significant tests show a degree of significance of 0.022 less than 0.05 (0.022 < 0.05) and the principle of justice has a significant positive effect on tax compliance. This result can be proven by value t-count > t-tables (3.276 > 2.017) and significant test results show a degree of significance of 0.002 smaller than 0.05.